Activity patterns, blood lactate concentrations and ratings of perceived exertion during a professional singles tennis tournament - Mendez-Villanueva, A.; Fernandez-Fernandez, J.; Bishop, D.; Fernandez-Garcia, B.; Terrados, N. (British Journal of Sports Medicine, 2007)
Objective: To examine the game characteristics and physiological (ie, blood lactate concentration) and perceptual (ie, rating of perceived exertion, RPE) responses during actual tennis competition in professional performers.